Language intervention to facilitate the acquisition of English as a second langauge by pre-school children. - Jordaan, Heila Letitia. (My University, 1993)
This dissertation explores the role of the speech-language therapist in second language acquisition. The motivation for the study arose out of recent political changes in South Africa, which led to desegregated education, and the need for young children to cope with English as the medium of instruction from the start of their schooling. The aim was to determine whether language intervention provided by a speech-language therapist significantly improved the English proficiency of a group of black pre-school children. A pre-test, post-test, centrol group experimental design was employed. The comprehension and expression of English vocabulary and syntax of thirty, three to six year old subjects was assessed using a modified version of the Test of Auditory Comprehension of Language-Revised (Carrow, 3.988), a newly devised vocabulary measure, as well as crystal's (1982) Profile in Lexical Semantics, and the Language Assessment Remediation and Screening Procedure (crystal et aL, 1989). The results showed that the English proficiency of the group of children who received language intervention from a speech-language therapist, improved significantly more than that of the first control group, who received only additional input in English, and the second control group, who received no input beyond that provided through the regular pre-school programme. The positive results of this research can now be applied to the teaching of languages other than English, and the training of teachers who would like to improve their skills at facilitating language acquisition.
A Dissertation Submitted to the Faculty of Arts University of the Witwatersrand, Johannesburg in partial fulfilment for the Degree of Master of Arts in Speech-Language Pathology.
Keywords: Second language acquisition.; English language -- Study and teaching (Preschool) -- South Africa -- Foreign speakers.; Speech therapy for children.